2016
DOI: 10.1055/s-0036-1583757
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Level of Post-menopausal Women with Low Bone Mineral Density

Abstract: Introduction Proper physical activity is related to the prevention and the treatment of osteoporosis. Purpose To assess the level of physical activity (PA) in post-menopausal women with low bone mineral density (BMD). Methods This cross-sectional clinical study included 123 post-menopausal women. The inclusion criteria were: age of ≥ 45 years with last menses at least 12 months prior to the initiation of the study, and bone density scan (BDS) values measured over the preceding 12 months. Women with severe oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
(21 reference statements)
0
11
0
6
Order By: Relevance
“…IPAQ is used in many recent studies to measure physical activity level of post-menopausal women [21] breast cancer patients (Canário, et al,1992), cardiovascular disease patients [22] and diabetes [23,24]. Turkish versions of the IPAQ short and long forms are found reliable and valid in assessment of physical activity [5].…”
Section: Discussionmentioning
confidence: 99%
“…IPAQ is used in many recent studies to measure physical activity level of post-menopausal women [21] breast cancer patients (Canário, et al,1992), cardiovascular disease patients [22] and diabetes [23,24]. Turkish versions of the IPAQ short and long forms are found reliable and valid in assessment of physical activity [5].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, physical activity seems to play an important role in maintaining skeletal health homeostasis by stimulating bone formation, through a mechanical action on osteoblasts and osteocytes [44,45]. In addition, some recent studies seem to support a role of physical activity in the modulation of sera soluble factors, which might act on skeletal cells improving bone homeostasis [46].…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome is defined as a set of metabolic changes that generate successive dysfunctions in lipid and glycemic levels, promoting the development of diseases such as visceral fat deposition (central obesity), insulin resistance and dyslipidemia. Hypoestrogenism is one of the causes related to the onset of metabolic syndrome, altering endocrine metabolism, with consequences for body weight gain, selective fat deposition and changes in lipid profile 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms that promote reduced estrogen plasma levels have not yet been clearly elucidated. However, research has indicated that estrogen plays an important role in the uptake of low-density lipoprotein (LDL) cholesterol by the liver, reducing their circulating values 5,6 . Estrogen also promotes increased lipoprotein lipase activity, an enzyme that increases fat lipolysis and contributes to reduced fat accumulation and triglyceride levels 6 .…”
Section: Introductionmentioning
confidence: 99%